Study of adsorption of biological and nanoparticle solutions at the solid-liquid interface - Frost, Daniel Wayne (Kansas State University, 2007)
With advances in micromechanical machining and nanotechnology, the sample volume needed for biological research and other analysis decreases. With small volume, sample-surface interactions including adsorption must be considered. These adsorption effects can be observed by analyzing light reflected from the solid-liquid interface, and the contact angle of a solution on the surface. Presented is the design and construction of an ellipsometer, a device used to analyze light reflected off of a solid-liquid interface to find interfacial properties, including thickness of a thin film formed by adsorption. The taq enzyme is shown to have a large change in contact angle from seventy degrees to about ten degrees over a short (ten minute) time period when placed on an SU-8 substrate, indicating a change in energy at the interface and a large amount of adsorption. Silane substrates are found to produce similar results. Ellipticity of a colloidal gold nanoparticle solution on a glass substrate is also observed, whose results are difficult to interpret due to bulk shifts in the sample. With the ellipsometer running correctly, it can be used for a number of experiments, including spectroscopic ellipsometry and Brewster angle microscopy, with some modifications.
Keywords: Ellipsometry; Adsorption; Contact angle; Physics, Condensed Matter (0611)